OpenVirtualObjects: An Open Set of Standardized and Validated 3D Household Objects for Virtual Reality-Based Research, Assessment, and Therapy - Tromp, Johanne; Klotzsche, Felix; Krohn, Stephan; Akbal, Mert; Pohl, Leonardo; Quinque, Eva M.; Belger, Julia; Villringer, Arno; Gaebler, Michael (Frontiers in Virtual Reality, 2020)
Virtual reality (VR) technology provides clinicians, therapists, and researchers with new opportunities to observe, assess, and train behaviour in realistic yet well-controlled environments. However, VR also comes with a number of challenges. For example, compared to more abstract experiments and tests on 2D computer screens, VR-based tasks are more complex to create, which can make it more expensive and time-consuming. One way to overcome these challenges is to create, standardize, and validate VR content and to make it openly available for researchers and clinicians. Here we introduce the OpenVirtualObjects (OVO), a set of 124 realistic 3D household objects that people encounter and use in their everyday lives. The objects were rated by 34 younger and 25 older adults for recognizability, familiarity, details (i.e., visual complexity), contact, and usage (i.e., frequency of usage in daily life). All participants also named and categorized the objects. We provide the data and the experiment- and analysis code online. With OVO, we hope to facilitate VR-based research and clinical applications. Easy and free availability of standardized and validated 3D objects can support systematic VR-based studies and the development of VR-based diagnostics and therapeutic tools.